An "ingenious system of practical contacts": Historical origins and development of the Institute of Child Welfare Research at Columbia University's Teachers College (1922–36) - Fierro, Catriel (2021)
During the first two decades of the 20th century, the expansion of private foundations and philanthropic initiatives in the United States converged with a comprehensive, nationwide agenda of progressive education and post-war social reconstruction that situated childhood at its core. From 1924 to 1928, the Laura Spelman Rockefeller Memorial was the main foundation behind the aggressive, systematic funding of the child development movement in North America. A pioneering institution, the Institute of Child Welfare Research, established in 1924 at Columbia's Teachers College, was the first Rockefeller-funded programme of its kind at an American university. The Institute was influential in helping set up a nationwide network of child welfare institutes at other universities. Twelve years later, it would also be the first of those institutes to close. Nonetheless, the Institute's context, emergence, and development have been overlooked or misrepresented by previous scholarship, which calls for a new, critical historical analysis. By drawing on a number of archival sources and unpublished materials, this paper offers a critical reconstruction of the Institute's internal, often unstable history, emphasizing its origins, members, and administrative changes. I argue that the demise of the Institute should be understood in the context of both the revision of philanthropic policies in the late 1920s and the Institute's singular emphasis on teaching and training over research. The resulting narrative allows for a deeper, more informed understanding of both the Institute's origins and its eventual folding.